Trade and structural adjustment embracing globalisation. (OECD, 2005)
This publication identifies the requirements for successful reallocation of labor and capital to more efficient uses in response to the emergence of new sources of competition, technological change and shifting consumer preferences. At the same time, it focuses on limiting adjustment costs for individuals, communities and society as a whole. Based on specific sectoral case studies, this volume includes analysis of the adjustment challenge and policy framework in both developed and developing countries, together with practical recommendations for good practice.--Publisher's description.